Iron status and obesity-related traits: A two-sample bidirectional Mendelian randomization study - Zhou, Zengyuan; Zhang, Hanyu; Chen, Ke; Liu, Changqi (Frontiers in Endocrinology, 2023)
Background: An association between iron status and obesity-related traits is well established from observational studies, however, the causality is uncertain. Here, we performed a two-sample bidirectional Mendelian randomization analysis to investigate the causal link between iron status and obesity-related traits. Methods: This study obtained the genetic variants through a series of screening processes from the summary data of genome-wide association studies in Europe. We used numerous MR analytical methods, such as inverse-variance weighting (IVW), MR-Egger, weighted median, and maximum likelihood, to make the conclusions more robust and credible, with alternate methods (including the MR-Egger intercept test, Cochran's Q test, and leave-one-out analysis) to evaluate the horizontal pleiotropy and heterogeneities of these genetic variants. In addition, the MR-PRESSO and RadialMR methods were utilized to identify and remove outliers, eventually achieving reduced heterogeneity and horizontal pleiotropy. Results: The results of IVW analysis indicated a significant positive association between body mass index (BMI) and serum ferritin (β: 0.077, 95%CI: 0.038, 0.116, P=1.18E-04) and a negative association between BMI and serum iron (β: -0.066, 95%CI: -0.106, -0.026, P=0.001) or transferrin saturation (TSAT) (β: -0.080, 95%CI: -0.124, -0.037, P=3.08E-04), but not total iron-binding capacity (TIBC). However, the genetically predicted waist and hip ratio (WHR) was not associated with iron status. Genetically instrumented iron status had no causal effect on BMI or WHR. Conclusions: In Europeans, BMI may be a causal factor in serum ferritin, serum iron, and TSAT, but the iron status does not cause a change in BMI or WHR.